Measuring vital signs temperature, pulse, respiration and blood pressure - Eighmy, Judith B.; Medcom, inc. (Cypress, CA : Medcom Trainex, 1997)
(Producer) Covers: reading a thermometer, measuring an oral temperature, measuring a rectal temperature, measuring axillary temperature, using an electronic thermometer, other methods of measuring temperature, measuring radial pulse, measuring respirations, and measuring blood pressure
Consultants, Judith B. Eighmy, Mary K. Keegan, Marianne McBrien
Keywords: Physical Examination -- nursing; Blood Pressure Determination -- nursing; Body temperature; Pulse; Respiration; Thermometers